(untitled) (Revista de Educação Pública, 2012)
Partindo de um processo de luta para conquista da terra de um assentamento do MST e da construção de sua territorialidade procuraremos compreender neste artigo, o modo como esta luta contribuiu para a formação de novos sujeitos políticos. A estrutura analítica está ancorada na categoria sociológica fronteiras/ margens e no quadro teórico Sociologia das Ausências de Boaventura de Sousa Santos, que permite visibilizar, com maior riqueza sociológica as experiências de lutas por emancipação social. As nossas conclusões apontam para processos pedagógicos intensos que dão conta da construção de subjetividades rebeldes que transformam quotidianos de exclusão em quotidianos de emancipação. The pedagogy that emerges of the political fight of MST Abstract Leaving of a fight process for conquest of the land of in an establishment of MST and of the construction of its territoriality we will try to understand this paper, the way as this fight contributed to the formation of new political subjects. Working with the bordering sociological categories/edges and the theoretical picture of the Sociology of the Absences of Boaventura de Sousa Santos, that it allows show, with larger sociological wealth the experiences of fights for social emancipation, we intended to create analytical conditions to understand pedagogic processes that give construction of rebellious subjectivities wich transform daily of exclusion in daily of fight and emancipation. Keywords: Social movements